Outcomes of Different Ablation Approaches for Para-Hisian Accessory Pathway and Ablation Safety at Each Site - Yang, Jian-du; Sun, Qi; Guo, Xiao-gang; Zhou, Gong-bu; Liu, Xu; Wei, Hui-qiang; Xie, Hai-yang; Ma, Jian (Frontiers in Cardiovascular Medicine, 2022)
Background This study describes the electrophysiologic characteristics of the para-hisian accessory pathway (AP), the outcome of different ablation approaches, and ablation safety at different sites. Method A total of 120 patients diagnosed as para-hisian AP were included in this study. The electrophysiologic characteristics and outcomes at different ablation sites were analyzed. Results In total, 107 APs and 13 APs were diagnosed as right anteroseptal (RAS) and right midseptal (RMS), respectively. The significant ECG difference between RAS and RMS was lead III, which mainly manifested as positive and negative delta waves, respectively. Catheter trauma to AP was recorded in 21 of 120 (17.5%) patients. The recurrence rate of direct ablation at the “bumped” sites was higher than the conventional ablation method (37.5 vs. 14.1 %, p = 0.036). For RAS APs, there was no significant difference in the success rate between the inferior vena cava (IVC) and superior vena cava (SVC) approaches (76.6 vs. 73.3%, p = 0.63). The RAS was separated into three regions: (1) Site 1: superior part above the real “His” recorded site with far-field “His” potential; (2) Site 2 (true para-hisian): the site with near-field “His” potential; and (3) Site 3: inferior part below the biggest real “His” with far-field “His” potential. Mid-septal was defined as an area that is bounded anteriorly by His recording location and posteriorly by the roof of coronary sinus (CS) ostium. The incidence of atrioventricular (AV) conduction injury at different sites was as follows: 3 of 6 (50%) at Site 2, 4 of 13 (30.8%) at RMS, 7 of 34 (20.6%) at Site 3, and 3 of 46 (6.5%) at Site 1. Even if ablation was performed at the atrial side of the para-hisian region, the right bundle branch block (RBBB) was caused in 6 patients (5%). Conclusion Ablation via IVC or SVC was comparative for para-hisian APs, but not for the noncoronary cusp (NCC) approach. The AV conduction injury risk ranks as follows: Site 2 > RMS > Site 3 > Site 1. RBBB could be caused while ablating at the atrial side, which could further demonstrate the His bundle longitudinal dissociation theory.